Impact of Pandemic – COVID 19 in Agrarian Part of the Country – A Study across Villages Adopted by Mount Carmel College, Autonomous, Bangalore - Dr. Govinda Gowda HG (International Journal of Engineering and Management Research, 2021)
This paper is showing that COVID19 has affected all walks of life. Protecting lives of people suffering from the disease as well as frontline health responders have been the priority of nations. Governments have swung into actions since the Corona virus attack created an unprecedented situation. India declared a three-week nation-wide lockdown till mid-April in the initial phase, which was subsequently extended for achieving satisfactory containment of the virus spread.